Research on Security of Virtualization on Cloud Computing - Xiaodi Wang; Yunyong Zhang; Di Liu; Ni Zhang; Yiming Yu (Dianxin kexue)
In recent years，followed by developing and popularizing of cloud computing service，the security problems appear. One of the problems，virtualization security，draws most attention of cloud services providers and security manufacturers. The main security threats of cloud computing virtualization environment were combed and cloud computing virtualization security technology architecture which contains virtualization security technology framework based on KVM and virtualization centralized management and control platform was proposed. Also WoCloud security management platform prototype system was developed according to technical architecture，and theoretical verification for cloud computing virtualization security technology architecture was carried out.